Study of Pitting Resistance of Rebar Steels in Jakarta Coastal Using Simulated Concrete Pore Solution. (2017) - Anwar, Moch. Syaiful; Fadillah, Bobby; Nikitasari, Arini; Oediyani, Soesaptri; Mabruri, Efendi
Abstract: Carbon steels are generally used to a reinforcement in the concrete constructions, such as bridges, piling, etc. These constructions are not a bit placed in the coastal areas, especially the coastal area of Jakarta. The industrial activities and urban development were a source of sediment loads and pollutants in coastal sea water Jakarta. The presence of chloride content and pollutants in sea water could affect the process of corrosion of reinforcement steel in concrete especially pitting corrosion. In this paper, the behavior of pitting corrosion of reinforcement steel in sea water of Jakarta coastal using simulated concrete pore solution has been studied. The sea waters were taken from two different locations of Jakarta coastal, Ancol beach and Muara Baru fishing port. Each of the sea water was used as a solvent in the simulated concrete pore solution with or without carbonates. The simulated concrete pore solution with chloride was also utilized for comparison test. The cyclic and potentiostatic electrochemical polarization were conducted to evaluate the behavior of pitting corrosion of reinforcing steel. The experimental results showed that the reinforcing steel was susceptible to pitting corrosion in the simulated concrete pore solutions (SPS) of sea water with or without carbonates and in the simulated concrete pore solutions containing 3.5% NaCl. The addition of sodium carbonate and sodium bicarbonate in SPS of sea water increased the breakdown potential value and the total time for the metastable pitting decreased slightly.